Correction: Cardiovascular Health in India – a Report Card from Three Urban and Rural Surveys of 22, 144 Adults. Issue 1 (22nd September 2022) - Shivashankar, Roopa; Singh, Kalpana; Kondal, Dimple; Gupta, Ruby; Perel, Pablo; Kapoor, Deksha; Jindal, Devraj; Mohan, Sailesh; Pradeepa, Rajendra; Jarhyan, Prashant; Venkateshmurthy, Nikhil Srinivasapura; Tandon, Nikhil; et al.
This article details a correction to: Shivashankar R, Singh K, Kondal D, Gupta R, Perel P, Kapoor D, et al.. Cardiovascular Health in India – a Report Card from Three Urban and Rural Surveys of 22, 144 Adults. Global Heart. 2022; 17(1): 52. DOI:http://doi.org/10.5334/gh.1137